Development of a new skeletal mechanism for decalin oxidation under engine relevant conditions. (15th January 2018) - Yu, Wenbin; Yang, Wenming; Tay, Kunlin; Zhao, Feiyang
Highlights: A skeletal mechanism was developed for decalin oxidation containing 42 species and 163 reactions. The decoupling methodology was used. Validations of the skeletal mechanism were conducted under engine relevant conditions. Abstract: Being one typical cyclo-alkane class component of commercial jet and diesel fuels, decalin has two fused six-membered rings and so far few studies of decalin were accessible to its oxidation mechanism. So that this study aims to propose a skeletal mechanism of decalin oxidation that facilitates the formulating of surrogate fuels applicable in power device like engines. In this study, a skeletal mechanism of decalin oxidation was developed based on the decoupling methodology. It contains 42 species and 163 reactions, in which a simplified mechanism for the oxidation of C2 –C10 is used to model the oxidation of heavy hydrocarbons for the prediction of the ignition characteristics, while the mechanism of H2 /CO/C1 was considered in details for the prediction of intermediate species concentrations. Among all intermediate combustion products, C2 H2 is designated as the most important soot precursor and will be used to predict soot tendency in the future study. The present skeletal mechanism was extensively validated against available fundamental experiments in regard of decalin oxidation under engine relevant conditions, wherein the temperature and pressure were relatively high. The computational results indicated that the predicted ignition delay in shock tubes and species concentrations in jet stirred reactors as well as in laminar premixed flames agree reasonably well with the measurements.